2017
DOI: 10.1016/j.chom.2017.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immunity to Intracellular Pathogens: Balancing Microbial Elimination and Inflammation

Abstract: Summary Recent excitement regarding immune clearance of intracellular microorganisms has focused on two systems that maintain cellular homeostasis. One system includes cellular autophagy components that mediate degradation of pathogens in membrane-bound compartments, in a process termed xenophagy. The second system is driven by interferon– regulated GTPases that promote rupture of pathogen-containing vacuoles and microbial degradation. In the case of xenophagy, pathogen sequestration and compartmentalization s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 86 publications
6
87
0
Order By: Relevance
“…EVs from M.tb ‐infected macrophages promoted phagosome maturation in M.tb ‐infected macrophages when used as pretreatment agent or after an M.tb infection, leading to reduced mycobacterial replication. Our results also found that EVs from M.tb ‐infected macrophages trigger M.tb ‐containing phagosome maturation through a LC3‐associated pathway . LAP represents an alternative autophagy‐dependent antimicrobial pathway in host cells, where LC3‐modified vesicles fuse with lysosomes, promoting microbial degradation .…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…EVs from M.tb ‐infected macrophages promoted phagosome maturation in M.tb ‐infected macrophages when used as pretreatment agent or after an M.tb infection, leading to reduced mycobacterial replication. Our results also found that EVs from M.tb ‐infected macrophages trigger M.tb ‐containing phagosome maturation through a LC3‐associated pathway . LAP represents an alternative autophagy‐dependent antimicrobial pathway in host cells, where LC3‐modified vesicles fuse with lysosomes, promoting microbial degradation .…”
Section: Discussionsupporting
confidence: 72%
“…Our results also found that EVs from M.tb-infected macrophages trigger M.tb-containing phagosome maturation through a LC3-associated pathway [26]. LAP represents an alternative autophagy-dependent antimicrobial pathway in host cells, where LC3-modified vesicles fuse with lysosomes, promoting microbial degradation [26]. Unlike classical autophagy, LAP is a Ubindependent process and only utilizes a subset of autophagy machinery components for the modification of microbe-containing vesicles by the LC3-conjugation system [27,28].…”
Section: Intra-tracheal Ev Administrationsupporting
confidence: 78%
“…Nuclear TFEB activates transcription of autophagy and lysosome genes, and induces autophagosome formation and lysosome biogenesis to upregulate flux through the macro-autophagy pathway. These lysosomal degradative processes generate nutrients that provide energy and support various metabolic functions (reviewed in (98)), and destroy invading organisms in immune cells via the process of xenophagy and enable antigen presentation to mount an immune response (reviewed in (136). …”
Section: Figurementioning
confidence: 99%
“…This division can be, however, blurrier as some intravacuolar pathogens, such as S . Typhimurium, can still access the host cytosol …”
Section: Introductionmentioning
confidence: 99%